Social work and the psychosocial effects of the economic crisis in Greece: challenges for new radical directions in services, theory and values - Charis, Asimopoulos; Teloni, Dimitra-Dora (Comunitania. Revista Internacional de Trabajo Social y Ciencias Sociales, 2017)
La crisis económica de Grecia provoca serios problemas sociales (aumento repentino del desempleo, inseguridad laboral, endeudamiento de los hogares, pobreza y desigualdad, mayor exclusión social y recortes significativos en salud, salud mental y sistema de protección social) que tienen efectos significativos sobre la situación psicosocial de la población (aumento de la depresión, ansiedad, problemas psicosomáticos, abuso de alcohol y suicidio). Los efectos psicosociales de la crisis económica han establecido nuevos estándares y exigencias para el trabajo social en Grecia y para el papel de los trabajadores sociales y los servicios sociales, especialmente a dos niveles: a nivel de servicio y valores y a nivel teórico. Los trabajadores sociales, en todos los entornos, deben estar en condiciones de tratar los problemas de salud mental con las intervenciones clínicas y comunitarias apropiadas, así como con un enfoque radical y métodos eficaces. The economic crisis in Greece cause serious social problems (sudden increase in unemployment, job insecurity, in household debt, in poverty and inequality, greater social seclusion and significant cutbacks in health, mental health and social protection system) that have significant effects on the psychosocial situation of the population (increase of depression, anxiety, psychosomatic issues, alcohol abuse and suicide). The psychosocial effects of the economic crisis have set new standards and demands for social work in Greece and for the role of the social workers and the social services, on two levels especially: service level and value and theory level. Social workers in all settings need to be in a position to deal with mental health problems with the appropriate clinical and community interventions as well as with radical approach and effective methods.